2022
DOI: 10.1007/s44150-022-00067-4
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the features of self-compacting rubberized concrete in the fresh and hardened states

Abstract: The rapid growth of urbanization and revolutionary improvement in the transportation industry paves the way for boosting tire production and generating a massive amount of waste tires every year. Waste tire disposal and proper maintenance have become a global concern because of the harmful chemical composition that conveys the potential to create an ecological imbalance that jeopardizes the world. One of the most powerful options is to ease the global problem by using recycled waste tires in the construction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 123 publications
0
0
0
Order By: Relevance
“…Several studies [34,36,37] suggested pretreating the crumb rubber with NaOH to roughen the surface and increase the interlocking bonding between the cement matrix and crumb rubber or adding mineral admixtures (such as fly ash, and silica fume, macro, and nano size to reduce porosity) improve compressive strength and microstructure [38]. A few researchers [39][40][41] revealed that the weakening of ITZ is mainly caused by coarse aggregate reducing the mechanical strength, whether compressive, flexural, or even elastic modulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [34,36,37] suggested pretreating the crumb rubber with NaOH to roughen the surface and increase the interlocking bonding between the cement matrix and crumb rubber or adding mineral admixtures (such as fly ash, and silica fume, macro, and nano size to reduce porosity) improve compressive strength and microstructure [38]. A few researchers [39][40][41] revealed that the weakening of ITZ is mainly caused by coarse aggregate reducing the mechanical strength, whether compressive, flexural, or even elastic modulus.…”
Section: Introductionmentioning
confidence: 99%
“…For the trending concrete types such as SCC and RCC, the crumb rubber has revealed different guides on whether to replace coarse or fine aggregate for better strength performance of the concrete. Table 1 and Table 2 [65][66][67][68][69][70][71][72][73][74] were generated by summing up collected data from the existing literature review showing the replacement of fine, coarse, and combined aggregate with crumb rubber in SCC [39] and RCC. Most researchers agree that replacing the rubber with fine aggregate in the case of SCC would be more beneficial than the coarse or total aggregate.…”
Section: Introductionmentioning
confidence: 99%